Prevalence of human cytomegalovirus disease and its related factors in renal and bone marrow transplant recipients in a tertiary hospital, Malaysia - Mastuki, Mohd Fahmi; Camalxaman, Siti Nazrina; Idris, Salmah; Mohd Lila, Mohd Azmi; Masri, Siti Norbaya; Mohd Taib, Niazlin (Universiti Sultan Zainal Abidin, 2022)
Human cytomegalovirus (HCMV) infection may cause substantial morbidity and mortality after renal and bone marrow transplantation [1]. There are 3 major consequences of HCMV infection: HCMV disease with a wide range of clinical illnesses; superinfection with opportunistic pathogens; and injury to the transplanted organ [2]. Other than serological method to diagnose HCMV infection, viral load quantitation by real time polymerase chain reaction has been widely appreciated to diagnose and monitor the progress of viral infections. The aims of this study were to determine the incidence of HCMV infection in renal and bone marrow transplant recipients and to investigate its associations with HCMV disease, gender, and races. This retrospective cohort analysis involved 1520 blood samples from transplant recipients (renal, n = 164 and bone marrow, n = 182) from January 2020 to December 2021 collected from Virology Unit, Hospital Kuala Lumpur (NMRR ethical approval: NMRR-20-993-53201(IIR). The samples were analysed with quantitative polymerase chain reaction for HCMV DNA and the demographic, clinical and paraclinical aspects were evaluated. HCMV infection was present if the patient had positive HCMV viraemia and HCMV disease was diagnosed if HCMV infection was followed by clinical signs and symptoms. Statistical comparisons of patient demographics were performed with Chi-square tests for the categorical variables. The overall incidence of HCMV infection in the study group was 65% (225/346) where renal and bone marrow transplants account for 78.2% (176/225) and 21.7% (49/225) respectively. The incidence of HCMV infection in renal transplantation differed significantly by sex (p<0.05) where it was higher in males (71.8%) than in females (28.2%) but there was not statistically significant by sex in bone marrow transplantation in which males and females account for 61.2% and 38.7% respectively. The incidence of HCMV differed significantly (p<0.05) by races in both transplantation types as follows: 58% in Malay, 36% in Chinese, 5% in Indian and 1% in other indigenous races in renal transplantation while 59% in Malay, 29% in Chinese, 10% in Indian and 2% in other indigenous races in bone marrow transplantation. The incidence of HCMV disease differed significantly (p<0.05) by type of transplantation where it is higher in renal transplantation (30.9%) than in bone marrow transplantation (20.2%). The most seen symptoms were fever, generalised lethargy, and headache. Viral load of HCMV has been shown to be a major determinant factor in the severity and the manifestation of the HCMV infection[3]. It is significantly higher in patients who develop HCMV disease[3]. Various risk factors have been described for the progress of symptomatic HCMV infection in organ transplant recipient[3]. The incidence of HCMV infection was higher in renal transplant as compared to bone marrow transplant among Malaysian. This study has shown that HCMV viral load has a significant association with age, gender and HCMV disease. Various syndromes can be caused by HCMV ranging from a mild fever to severe end-organ diseases. Treatment with anti-HCMV therapy results in decline in HCMV load, usually to undetectable.